Dynamics of National Composition of Vilnius Population in the 2nd Half of the 20th Century - Stanaitis, Saulius; Česnavičius, Darius (Bulletin of Geography. Socio-economic Series, 2010)
The article presents changes of national composition of Vilnius population in the 2nd half of the 20th century. The changes of Vilnius population are analyzed with respect to nationality, including the smallest territorial administrative units of Vilnius. The growth of the city population was associated with an intensive allround city development. Based on the data of the censuses of 1989 and 2001, the article focuses on the dynamics of national composition, which took place after the restoration of independence. The analysis encompasses not only the intensity of dynamics of different nationalities but also the portion of national minorities residing in Vilnius (Poles and Russians in particular) on a country scale.